Evidence for long‐lasting alterations in the fecal microbiota following prenatal alcohol exposure. (17th February 2022) - Bodnar, Tamara S.; Lee, Christopher; Wong, Athena; Rubin, Ilan; Wegener Parfrey, Laura; Weinberg, Joanne
Abstract: Background: There is growing evidence that the gut microbiota can be shaped by early‐life experiences/exposures, with long‐term consequences for brain, behavior, and health. Changes in the gut microbiota have also been identified in neurodevelopmental disorders including Autism Spectrum Disorder and schizophrenia. In contrast, no studies to date have investigated whether the gut microbiota is altered in individuals with Fetal Alcohol Spectrum Disorder (FASD), the neurodevelopmental disorder that results from prenatal alcohol exposure (PAE). The current study was designed to assess the impact of PAE on the fecal microbiota. Methods: We used a rodent model in which pregnant Sprague–Dawley rats were provided with an EtOH‐containing diet or a control diet throughout gestation. Fecal samples were collected from adult male and female animals and 16s rRNA sequencing was performed. Results: Overall, PAE rats showed greater richness of bacterial species, with community structure investigations demonstrating distinct clustering by prenatal treatment. In addition, prenatal treatment and sex‐specific alterations were observed for many specific microbes. For example, in males, Bacteroides and Bifidobacterium, and in females, Faecalitalea and Proteus, differed in abundance between PAE and control rats. Conclusions: Taken together, these results show for the first time that PAE has a long‐lasting and sex‐specific impact on the fecal microbiota. Further research is needed that considers fetal microbiota in the development of new interventions in FASD. Abstract : Microbiota alterations have been identified in several neurodevelopmental disorders; however, to date, no studies have investigated whether microbiota changes occur following prenatal alcohol exposure (PAE). Here, we used a rodent model with pregnant dams exposed to a liquid ethanol or control diet, and fecal samples collected in adulthood for 16s rRNA sequencing. Our results show that PAE resulted in long‐lasting microbiota changes, with differential outcomes in males and females. These findings have implications for possible novel microbiota‐based interventions following PAE.